2017
DOI: 10.1182/blood-2016-06-724658
|View full text |Cite
|
Sign up to set email alerts
|

Acquired expression of CblQ367P in mice induces dysplastic myelopoiesis mimicking chronic myelomonocytic leukemia

Abstract: Key Points Acquired expression of CblQ367P induces sustained proliferation of myelomonocytes, multilineage dysplasia, and splenomegaly resembling CMML. Combined inhibition of PI3K and JAK2 efficiently suppressed the growth of CblQ367P-induced CMML cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 53 publications
(65 reference statements)
2
14
1
Order By: Relevance
“…A JAK2 inhibitor was reported to be effective in a mouse model of Cbl-deficient chronic myelomonocytic leukemia expressing JAK2. 27 Together with the results of previous studies, our findings raised a question regarding the activity of JAK2 inhibitors in TSGCT patients with CBL mutations. These inhibitors currently have therapeutic applications in the treatment of myelofibrosis or inflammatory diseases such as rheumatoid arthritis.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A JAK2 inhibitor was reported to be effective in a mouse model of Cbl-deficient chronic myelomonocytic leukemia expressing JAK2. 27 Together with the results of previous studies, our findings raised a question regarding the activity of JAK2 inhibitors in TSGCT patients with CBL mutations. These inhibitors currently have therapeutic applications in the treatment of myelofibrosis or inflammatory diseases such as rheumatoid arthritis.…”
Section: Discussionsupporting
confidence: 75%
“…Our analysis demonstrated that CBL mutations were associated with enhanced JAK2 expression and poor local disease control. A JAK2 inhibitor was reported to be effective in a mouse model of Cbl ‐deficient chronic myelomonocytic leukemia expressing JAK2 . Together with the results of previous studies, our findings raised a question regarding the activity of JAK2 inhibitors in TSGCT patients with CBL mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other studies that observed hyperactivation of MAPK, JAK-STAT and PI3K/AKT pathways (2,6,15,23,24,28,(35)(36)(37)(38)(39)(40)(41), our global characterization of tyrosine phosphorylation in cells expressing mutant CBL revealed selective activation of LYN and the PI3K/AKT pathway; in fact, tyrosine phosphorylation sites that directly indicate activation of the MAPK or STAT5 pathways were lower in our CBL mutant cells by MS analysis. There are several potential explanations for this discrepancy.…”
Section: Discussioncontrasting
confidence: 95%
“…Consistent with the genetics of CBL mutations in myeloid malignancies, missense mutations in the RING domain of murine Cbl promoted the development of a myeloproliferative disorder that was not observed in Cbl knockout mice (22)(23)(24).…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation